Expert consensus on the combination of anti-EGFR monoclonal antibodies and immune checkpoint inhibitors in the treatment of head and neck squamous cell carcinoma (2025 edition) - XUE Liqiong, XU Tingting, GUO Ye, HU Chaosu (Zhongguo aizheng zazhi, 2025)
Head and neck squamous cell carcinoma (HNSCC) is the most common type of head and neck cancer, and its treatment prognosis remains suboptimal. Although the survival of HNSCC patients has improved with the widespread use of anti-epidermal growth factor receptor (EGFR) monoclonal antibodies and immune checkpoint inhibitors (ICIs), there is still significant room for further improvement. Recent studies have suggested that the combination of anti-EGFR monoclonal antibodies and ICIs offers promising efficacy and safety, earning recommendations from authoritative guidelines such as the National Comprehensive Cancer Network (NCCN) and the Chinese Society of Clinical Oncology (CSCO). However, the application of this combination therapy is still in the early exploratory stage, numerous questions regarding the standardized clinical use of this combination therapy remain unanswered, including the mechanisms of synergy associated with the combination treatment, its therapeutic value in different patient populations, and safety considerations. Committee of Head and Neck Cancer, Chinese Society of Clinical Oncology organized an expert panel to develop “Expert consensus on the combination of anti-EGFR monoclonal antibodies and immune checkpoint inhibitors in the treatment of head and neck squamous cell carcinoma (2025 edition)”, based on evidence-based medicine and clinical practice exploration through multiple rounds of discussions. This consensus addressed the mechanisms of the combination of anti-EGFR monoclonal antibodies and ICIs, stratified treatment approaches, applications in special populations, and safety considerations. The consensus has been registered on Practice guideline REgistration for transPAREncy (PREPARE) with the registration number PREPARE-2025CN666. It is hoped that this consensus will provide clearer and more practical guidance for clinicians, further promoting the rational application of this combination therapy in clinical practice and offering more treatment options for HNSCC patients.